The first beam test of a monolithic particle pixel detector in high-voltage CMOS technology - Peric, Ivan; Takacs, C.; Behr, J.; Wagner, F. M.; Fischer, Peter (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2011)
The results of beam- and irradiation tests preformed on a monolithic particle pixel detector in high-voltage CMOS technology will be presented for the first time. All tested detectors are implemented in a 0.35μm technology, they utilize high-voltage n-well/p-substrate diodes as pixel sensors and rely on charge drift in diode depletion layers as the main signal generating mechanism. The detector prototype tested in the beam is a system on a chip that contains a 128×128 matrix with 21×21μm2 large pixels, source-follower based- rolling shutter readout and on-chip ADCs that digitize the signal amplitudes with 8-bit precision. Test beam measurements have been performed using EUDET infrastructure. The measured MIP cluster signals are typically 2200e, spatial resolution approximately 7μm (RMS), signal-to-noise ratio of a single pixel is 12.3 and detection efficiency more than 85%. To test the radiation tolerance, several detector chips have been irradiated with neutrons up to 1014neq/cm2 and with X-rays up to 500kGy (50Mrad), they are still functional and the experimental results obtained with these chips will be presented as well.